Volksrepublik China: Perspektiven für die Motorisierung im 21. Jahrhundert. - (:unkn) unknown (Deutscher Verkehrs-Verl., 2008)
Die Automobilisierung Chinas entwickelt sich zu einem der wichtigsten Wachstumsmotoren für die Modernisierung des Landes. Aber die chinesische Automobilindustrie hat noch einen erheblichen technologischen Rückstand. Gefördert von der BMW Group hat ein multidisziplinäres Forschungskonsortium unter Federführung des Wissenschaftszentrums Berlin für Sozialforschung (WZB) die Chancen und Risiken für die Automobilindustrie in China untersucht. Im Mittelpunkt stand dabei die Frage, ob die automobile Wasserstofftechnologie eine entscheidende Chance für China bietet, den Rückstand gegenüber den führenden Produzentenländern innerhalb von wenigen Jahren aufzuholen.

The PRC leadership's policy outlook has been reorientated from 'hyper' to 'balanced' growth together with a switch from 'low cost' to 'high tech' development. To achieve these goals, China's leadership follows a double-edged strategy aimed at modernizing the country and, in particular, its motor industry. Initially, a process of 'catching-up' on modernization is intended to reach the level of scientific and technical standards of the USA Japan and Europe by 2020. Further modernization is to surpass the West from 2020 onward and, using the leading position thus secured, to build up a global and comprehensive market leadership in science and technology by 2050. The 'catching-up' modernization of the motor industry's technological standards is in a relatively homogenous and self-contained way. Although the process of 'surpassing' the modernization of the motor industry's technological standards is less distinct, the success of the hydrogen research programme based on the Five-Year Plan has been such that, within the next fifteen years, China's potential for quantum leaps from 2020 onward may become a reality.
Motorization of China: perspectives for the 21st century.
Keywords: Verkehr; Verkehrsprognose; Verkehrstechnologie; Wasserstoff; Verkehrsinfrastruktur; Straßenverkehr; Motorisierung; Kraftfahrzeug; Automobilindustrie; Wasserstofftechnologie; Brennstoffzelle; Forschung und Entwicklung; Internationale Zusammenarbeit